A study of the temperature effect on Hantzsch reaction selectivity using Mn and Ce oxides under solvent-free conditions - D'alessandro, Oriana (2014)
In this communication, four materials (CeO2,CeO2(Cu), MnOx, and MnOx(Cu)) were prepared, characterized and tested as catalysts, in solvent-free conditions, for the multicomponent Hantzsch reactions to obtain alternatively the 1,4-dihydropyridine or 2-phenylpyridine depending on the reaction conditions. 1,4-Dihydropyridine 4 was the main product formed at 80 °C (76%), and 2-phenylpyridine7 was the main product at 40 °C (91%), inoxidant-free conditions, CeO2 catalyst. It is the first report that shows that, not only the temperature but also the nature of the catalyst may change the product selectivity in Hantzsch reactions.